Characterization of the bacterial microbiota of Biomphalaria glabrata (Say, 1818) (Mollusca: Gastropoda) from Brazil. (27th March 2013) - Silva, T.M.; Melo, E.S.; Lopes, A.C.S.; Veras, D.L.; Duarte, C.R.; Alves, L.C.; Brayner, F.A.
Abstract Roughly 200 000 000 people in 74 countries infected with schistosomes all share the fact that they came in contact freshwater harbouring infected snails. The aim of the study is to characterize the microbiota of wild and laboratory‐reared snails of Biomphalaria glabrata from Pernambuco, Brazil. The microbiota of these molluscs was identified biochemically by the VITEK 2 automated microbiological system. Antimicrobial susceptibility testing was carried out by the disc diffusion method with ß‐lactam antibiotics, aminoglycosides, quinolones, folate pathway inhibitors, fenicols and tetracyclines. The results showed that all bacteria identified were gram‐negative, including 11 bacterial genera: Aeromonas, Citrobacter, Enterobacter, Cupriavidus, Rhizobium, Stenotrophomonas, Pseudomonas, Klebsiella, Acinetobacter, Vibrio and Sphingomonas. Regarding the antimicrobial susceptibility, all the isolates exhibited resistance to amoxicillin and sensitivity to meropenem (beta‐lactam antimicrobials). The microbiota of the wild snails consisted predominantly of Enterobacter cloacae, while the laboratory‐reared snails predominantly showed Citrobacter freundii and Aeromonas sobria. Significance and Impact of the Study Biomphalaria glabrata is a Brazilian freshwater Planorbidae of great medical relevance as an intermediate host of Schistosoma mansoni. About a month after being infected by one or more miracidia larvae of a compatible schistosome, B. glabrata sheds thousands of cercariae into the water where they seek human skin and, if successful, penetrate to establish infection, eventually taking up residence and maturing in blood vessels of the small intestine. Results obtained from this study aim at targeting novel biological control strategies for schistosomiasis such as paratransgenesis. This is the first study on the microbiota of B. glabrata from Brazil.